2016
DOI: 10.1111/eth.12507
|View full text |Cite
|
Sign up to set email alerts
|

Do Female Western Mosquitofish,Gambusia affinis,Prefer Ornaments That Males Lack?

Abstract: Some species in the family Poeciliidae are known for extravagant male ornaments and courtship behavior (e.g., guppies), but the majority of poeciliids are characterized by coercive male copulation attempts that seem to circumvent female choice. In some lineages with male ornaments, female sensory bias may have preceded the evolution of corresponding male signals. We examined female preferences for colorful ornaments in Western mosquitofish, Gambusia affinis, in which males lack ornamentation and reproduce prim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 63 publications
0
4
0
Order By: Relevance
“…Even though females’ motivation to mate may decrease when fish are maintained in mixed-sex groups compared with virgins or females that had been isolated from mating partners for some time (e.g., several weeks [ 79 , 80 ], rearing or maintenance conditions do not necessarily affect individuals’ preferences for phenotypic traits of potential mating partners. Thus, studies on mate choice in mosquitofish widely used focal fish originating from mixed-sex tanks [ 36 , 81 83 ]. Aquaria were well equipped with plants, twigs and stones.…”
Section: Methodsmentioning
confidence: 99%
“…Even though females’ motivation to mate may decrease when fish are maintained in mixed-sex groups compared with virgins or females that had been isolated from mating partners for some time (e.g., several weeks [ 79 , 80 ], rearing or maintenance conditions do not necessarily affect individuals’ preferences for phenotypic traits of potential mating partners. Thus, studies on mate choice in mosquitofish widely used focal fish originating from mixed-sex tanks [ 36 , 81 83 ]. Aquaria were well equipped with plants, twigs and stones.…”
Section: Methodsmentioning
confidence: 99%
“…However, these studies quantified only copulations, not the siring of offspring, and both studies focused on species without courtship or male ornamentation. A number of additional studies have examined female preferences in species without courtship (McPeek, 1992;Basolo, 1998;Bisazza and Pilastro, 2000;MacLaren and Rowland, 2006;Casner et al, 2016). In nearly every case, females prefer a larger, more ornamented male, even when that male is not the same species as the female (Basolo, 1998).…”
Section: Variation Among Males and Associated Female Mating Preferencesmentioning
confidence: 99%
“…To date, research has only demonstrated that the western mosquitofish possesses all four phylogenetic classes of cone opsin genes, including two sws2 genes ( sws2a and sws2b ), but exactly how many cone opsins it has remains uncertain [ 32 ]. Moreover, previous studies indicate that the western mosquitofish may display ontogenetic changes in cone opsin expression profiles because it exhibits an ontogenetic dietary shift, colors are critical to it in the mating choice of both sexes, and sex steroid estrogen influences its cone opsin expression profiles [ 32 36 ].…”
Section: Introductionmentioning
confidence: 99%